2013
DOI: 10.1111/jbl.12012
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Supply Chain Agility: Conceptualization and Scale Development

Abstract: Although agility has been identified as one of the most important issues of contemporary supply chain management, the theoretical basis for understanding supply chain agility is fragmented. This research addresses the gap related to the ambiguity surrounding the dimensions and definitions of firm supply chain agility by employing a multidisciplinary literature review to gain an in‐depth understanding of agility. In addition, a comprehensive measurement instrument that draws on the foundations of social and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
330
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(346 citation statements)
references
References 94 publications
(254 reference statements)
5
330
1
10
Order By: Relevance
“…Agility in the supply chain context has gained importance as a critical and dominant supply chain capability (Gligor, Holcomb, & Stank, 2013). Initially, supply chain agility was explored mostly from a manufacturing standpoint using different perspectives (Gligor et al, 2013). Later, agility was extended to supply chains and targeted to increase speed and response in the supply chain with respect to the demands of the customers (Swafford, Ghosh, & Murthy, 2006) and hence related to the effectiveness of strategic supply chain management (Ketchen & Hult, 2007).…”
Section: Website Agilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Agility in the supply chain context has gained importance as a critical and dominant supply chain capability (Gligor, Holcomb, & Stank, 2013). Initially, supply chain agility was explored mostly from a manufacturing standpoint using different perspectives (Gligor et al, 2013). Later, agility was extended to supply chains and targeted to increase speed and response in the supply chain with respect to the demands of the customers (Swafford, Ghosh, & Murthy, 2006) and hence related to the effectiveness of strategic supply chain management (Ketchen & Hult, 2007).…”
Section: Website Agilitymentioning
confidence: 99%
“…Agility in the supply chain context has gained importance as a critical and dominant supply chain capability (Gligor, Holcomb, & Stank, 2013). Initially, supply chain agility was explored mostly from a manufacturing standpoint using different perspectives (Gligor et al, 2013).…”
Section: Website Agilitymentioning
confidence: 99%
“…Li et al [2] have reviewed some previously proposed definitions of supply chain agility and developed a theory-driven model that describes supply chain agility at various work design levels. Gligor et al [24] have indicated that supply chain agility is composed of alertness, accessibility, decisiveness, swiftness, and flexibility. Some factors that contribute to achieving agility in supply chain can be identified based on the fundamental elements of supply chain agility identified in these studies.…”
Section: Related Literaturementioning
confidence: 99%
“…The six dimensions were strategic alertness, strategic response capability, opera tional alertness, operational response capability, episodic alertness and episodic response capability. Finally, using foundations of social and life science theory Gligor et al (2013) developed a comprehensive measurement instru ment for SC agility. This showed SC agility is composed of five distinct dimensions including alertness, accessibility, decisiveness, swiftness, and flexibility.…”
Section: Agility In Supply Chains and E-retailer's Agilitymentioning
confidence: 99%